Relationship between shoulder forces, shoulder joint shear stress, and throwing velocity during baseball pitching - Naito, K.; Takagi, T.; Kubota, H.; Maruyama, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
It is well accepted that the anterior shoulder joint force generated in baseball pitching is a risk factor for throwing-related injuries. However, the exact mechanism that causes shoulder joint force is still unclear. This study aimed to clarify the mechanism underlying generation of shoulder shear stress, and gain knowledge about proper throwing mechanics that can minimise joint stress and maximise performance. To this end, the throwing motions of 16 male collegiate baseball pitchers were measured using a three-dimensional motion capture system. Subsequently, induced-joint force analysis and induced-segmental velocity analysis, developed in this study, were used to decompose the shoulder joint force and fingertip velocity of the throwing upper extremity into causal muscular and interactive torque components. Induced-joint force analysis showed that the muscular torque-induced component to the maximum anterior shoulder joint force accounts for more than 100%, and the shoulder horizontal adduction torque is the greatest contributor among all joints. Induced-segmental velocity analysis found that the centrifugal force effect was the largest contributor, at 42.3% of the maximum fingertip velocity. The current findings imply that effectively exploiting centrifugal force for throwing arm acceleration is the key factor for achieving proper throwing that maximises ball speed and minimises shoulder joint load.